Pengaruh Kredibilitas Public Relations Terhadap Tingkat Penerimaan Pesan Klarifikasi Aqua (Studi Kuantitatif Pada Khalayak Terkait Isu Sumber Mata Air Aqua) - Muhammad Rizal Khatami; Veny Purba; Rosanti Utami D.S Yatnosaputro (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
The rise of social media has enabled issues involving organizations to spread rapidly and generate diverse public responses. This was evident in the controversy surrounding AQUA’s water sources, which emerged after the circulation of a video of a surprise inspection uploaded by the Kang Dedi Mulyadi Channel on October 21, 2025. This issue was followed by a clarification statement from AQUA, which elicited differing responses among the public. This study aims to analyze the influence of AQUA’s public relations (PR) credibility on the level of acceptance of the clarification message regarding the AQUA water source issue among all respondents, as well as among the groups of the public that supported and opposed the statement. The study employs an explanatory quantitative approach using a survey method. Data were collected from 136 respondents who were aware of the AQUA water source issue and had seen the clarification message issued by AQUA. The results of the study indicate that the credibility of Public Relations has a significant effect on the level of acceptance of the clarification message among all respondents, with a regression coefficient of 1.202 and a coefficient of determination of 98.3%. A significant influence was also found among the supportive group, with a regression coefficient of 1.150 and an R² of 96.9%, as well as among the opposed group, with a regression coefficient of 1.211 and an R² of 87.6%. These findings indicate that the credibility of Public Relations plays an important role in message acceptance but is not yet fully capable of changing the attitudes of the public who already hold negative views on the issue.